Outcomes of Invasive Meningococcal Disease in Adults and Children in Canada Between 2002 and 2011: A Prospective Cohort Study. (20th January 2015) - Sadarangani, Manish; Scheifele, David W.; Halperin, Scott A.; Vaudry, Wendy; Le Saux, Nicole; Tsang, Raymond; Bettinger, Julie A.; ,; Bridger, N.; Morris, R.; Halperin, S.; Top, K.; et al.
Abstract : Outcomes following meningococcal disease remain poor in this resource-rich setting, with 27% of infections resulting in death or complications. Increased mortality was associated with shock, older age, and rapid symptom onset; admission to intensive care unit was a protective factor. Abstract: Background.   Neisseria meningitidis causes 500 000 cases of septicemia and meningitis worldwide annually, with approximately 200 cases in Canada each year. Previous studies describe a case-fatality rate of 5%–15% and up to 20% of survivors suffering from long-term disability. Methods.  This study was performed in Canada between 2002 and 2011; the study area included >50% of the country's population. We identified risk factors associated with death and the development of complications in children and adults admitted to hospital with confirmed invasive meningococcal disease (IMD). Clinical information was obtained from hospital records. Risk factors for death and complications were analyzed by univariate and multivariable analyses. Results.  Of 868 individuals hospitalized with IMD, there were 73 deaths (8.4%) and 157 (18%) developed complications. The most common complications were hearing loss (5.4%), skin scarring (5.4%), amputation (3.4%), renal dysfunction (2.6%), and seizures (2.5%). Mortality was independently associated with shock (adjusted odds ratio [aOR], 23.30; P < .0001), age (aOR, 1.02 per 1-year increased age; P < .0001), symptom onset within 24 hours of admission (aOR, 1.80; P = .0471), and admission to the intensive care unit (aOR, 0.41; P = .0196). Development of complications was independently associated with seizures (aOR, 4.55; P < .0001), shock (aOR, 3.10; P < .0001), abnormal platelet count (aOR, 2.14; P = .0002), bruising (aOR, 3.17; P = .0059), abnormal white blood cell count (aOR, 0.52; P = .0100), and prior antibiotic exposure (aOR, 0.27; P = .0273). Conclusions.  Outcomes following IMD remain poor in this resource-rich setting in the 21st century. These data identify priorities for clinical management of adults and children with IMD, and provide prognostic information for affected patients and their families and cost-effectiveness analyses for meningococcal vaccine programs.